Changes in Soil Microbiology Under Conventional and No-Till Production During Crop Rotation - C. J. Hsiao; G. F. Sassenrath; L. Zeglin; G. Hettiarachchi; C. Rice (Kansas Agricultural Experiment Station Research Reports, 2019)
Soil microbial activity is important for crop production. Soil microbes are involved in nutrient and water cycling within the soil, and interact with crop plants to provide the basic nutrient and water resources needed for crop production. Claypan soils have unique physical characteristics that impact soil biology. This study explored the temporal changes in soil microbiology in a claypan soil under conventional and no-till production during a crop rotation of corn/winter wheat/soybean/fallow commonly planted in southeast Kansas. We found soil microbial activity changed more in the top two inches of soil than in the lower soil layers. Wheat resulted in higher soil microbial activity and biomass than corn. Soybeans had a more stable microbial activity in the soil than either corn or wheat. The no-till plots had greater microbial biomass and activity than conventionally tilled systems, and the temporal changes in soil microbial properties were more apparent in no-till plots. These results offer an interesting insight into the soil biological properties that impact soil health for crop production.
Keywords: soil microbiology; soil health; crop production; temporal change